Belief System and Cultural Ways of Life: State of Knowledge of Cultural Research in the Northeast - Srisontisuk, Somsak; Norkaew, Yutthasart (Journal of Public Administration Chiang Rai Rajabhat University, 2024)
This article aims to present the belief system and cultural way of life from cultural research results that appear in the information search sources in the Northeast of Thailand by using the qualitative study method from searching for documents and various related research works to focus on answering the questions of cultural research in the Northeast about what common characteristics they have. The results of the study found that the knowledge frontier is the relationship between beliefs and cultural way of life that are significantly related and cannot be separated from each other. That is, the development of cultural knowledge requires studying various characteristics, including 1) components of the belief system, 2) the role of the belief system in the cultural way of life, 3) the dimensions of the belief system, and 4) the importance of the belief system that is beneficial to the cultural way of life.